2010
DOI: 10.1007/s10144-010-0252-3
|View full text |Cite
|
Sign up to set email alerts
|

Forest gene diversity is correlated with the composition and function of soil microbial communities

Abstract: The growing field of community and ecosystem genetics indicates that plant genotype and genotypic variation are important for structuring communities and ecosystem processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 97 publications
1
50
3
2
Order By: Relevance
“…; Schweitzer et al . ). This naturally occurring variation in the density of host species, but not overall host tree density, allowed us to evaluate how the density of the most susceptible Populus host species affects pathogen community structure.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Schweitzer et al . ). This naturally occurring variation in the density of host species, but not overall host tree density, allowed us to evaluate how the density of the most susceptible Populus host species affects pathogen community structure.…”
Section: Methodsmentioning
confidence: 97%
“…both parental species and their hybrids) did not differ among sites (Schweitzer et al . ), a second covariate included in hybrid zone analyses was the density of the susceptible host, P. angustifolia , which did differ among sites. A greater density of susceptible host species should increase the probability of successful infection by airborne inoculum (Burdon & Chilvers ).…”
Section: Methodsmentioning
confidence: 99%
“…Schweitzer et al [53] reported that plant gene diversity may alter soil microbial communities and their activities, which may have extended consequences for soil fertility. Patterns of soil microbial community are also dependent on soil moisture [54].…”
Section: Influence Of Land-use Change On the Soil Microbial Communitymentioning
confidence: 99%
“…It has been recognised that these interactions can affect plant productivity in agricultural systems and has lead to the concept of suppressive ecosystems that act to protect plants against pathogens including nematodes, bacteria and fungi. [17][18][19][20] Metagenomics is one approach that has been used to explore this aspect of soil communities. This work suggests that the analogous metametabolomic approaches may also provide valuable insight into this complex system.…”
Section: Discussionmentioning
confidence: 99%